Model kategorizacije autobusnih kolodvora - Štefančić, Gordana (Promet - Traffic&Transportation, 2012)
The author has in this paper offered for the first time in Croatia the model of classification of bus stations according to the following criteria: - daily number of services: departures and arrivals - percentage of transit bus services pyramid classification - geographical/traffic-aspected location of a particular bus station. The study has covered eleven bus stations, transit, transversal and terminal ones, dealing with a precise description of their transport functions, level of provision of infrastructure facilities and equipment, as well as their temporal by aspected operations. Classification provides the instruments for establishing the amount of the fee paid by transport companies for using the bus station and parking, and by passengers through booking seats and paying for bus station service, left luggage and use of toilets and parking of their automobiles. Classification sets to bus stations the requirement of provision of technological and engineering propositions to grant passengers and other users of bus stations a particular level of service.